Peningkatan Pengetahuan Kader Posyandu Tentang Stunting Pada Anak dengan Kartu Pintar Stunting - Dhiah Dwi Kusumawati; Rochany Septiyaningsih; Septiana Indratmoko (Jurnal Pengabdian kepada Masyarakat Cahaya Negeriku, 2022)
Background: Stunting is caused by lack of nutritional intake for a long time in the first 1000 days of life (HPK), which is a critical period. Therefore, it is necessary to do stunting prevention efforts launched by the government including pregnant women getting a minimum of 90 bloodadded tablets during pregnancy, giving additional food to pregnant women, fulfilling nutrition, giving birth with health workers, IMD, exclusive breastfeeding, giving complementary foods to breast milk, giving complete basic immunizations and vitamin A, monitor the growth of toddlers at the nearest posyandu, and apply clean and healthy lifestyle. Purpose: increase the knowledge of posyandu cadres so that they are able to prevent stunting. Method: The method of implementation in the community service program is by providing counseling about stunting to posyandu cadres, Sidanegara sub-district, Cilacap. Results: The results of the average value of knowledge of cadres during the pre test was 55. Then continued with the presentation of stunting. Ended by filling out the post test questionnaire with the result that the average value of cadre knowledge was 95. Conclusion: There is an increase in knowledge of Posyandu cadres about stunting in children in Sidanegara Village.